PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON-EXAMPLES TERHADAP HASIL BELAJAR SISWA - Astuti, Aprilia Tri; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â Abstract The purpose of this study is to know the influence of examples and non-examples type of cooperative learning model for increased student learning achievement on solid matter expansion. The form of study used quasi experimental with nonequivalent control group design. Data collection instrument in this study involved pretest and posttest that each of them Â question description to quantify of learning achievement. This study conducted in two classes consisting of experiment class and control class. For experiment class, samples were 31 students and for control class were 29 students. The result of this study showed that there was difference increase of students learning achievement between beingÂ taught with examples non-examples type of cooperative learning model and conventional learning model with P Value 1.07267x10-12 < from Î± = 0,05. Based on the results of this study can be recommended that examples and non examples type of cooperative learning model can be use as an alternative learning model to increase student learning achievement.Keywords: solid matter expansion, learning achievement, examples non-examples type of cooperative learning model.